S146 Microvascular endothelial cell apoptosis and dysregulation of Vascular Endothelial Growth Factor Receptor 2 (VEGF-R2) in response to cigarette smoke. New insights into the pathogenesis of emphysema. (16th November 2010) - Mackay, L S; Dodd, S; Tomlinson, W; Dougall, I; Walden, H; Isherwood, B; Gardner, A; Borthwick, L; Brown, K Pinnion; Foster, M; Fisher, A J; Corris, P A
Abstract : Microvascular injury may be a primary mechanism in the pathogenesis of emphysema. Rats treated with a VEGF-R2 antagonist develop emphysema that is caspase-3 dependent. Additionally, patients with emphysema have reduced VEGF. We hypothesised that cigarette smoke injury may disrupt homeostatic vascular repair mechanisms and investigated VEGF-R2 expression and endothelial apoptosis in the pulmonary microvasculature of patients with emphysema. Methods: Microvascular endothelial cells were isolated from explanted peripheral lung tissue from four patients with emphysema undergoing transplantation. Cells were characterised via flow cytometry and confocal microscopy. Concurrent immunolocalisation of CD31, VEGF, VEGF-R2 and caspase-3 was performed on peripheral lung tissue from each patient and expression compared with that in excess normal lung tissue obtained from lobectomies. Isolated endothelial cells were treated with freshly prepared cigarette smoke extract (CSE) (3%) for 0, 24, 48, 72 h and expression of VEGF-R2 investigated via q-PCR. A cell permeable caspase-3 substrate, NucView 488 (Biotium), which is cleaved by the enzyme to form a high-affinity fluorescent DNA binding dye, was used to detect apoptosis via live cell imaging in response to CSE (0–12%) over 64 h. Results: Isolated cells at low passage (P3-P6) expressed high levels of CD31, negligible CD90 and inducible CD62 confirming them as microvascular endothelial cells. VEGF-R2 expression was significantly reduced (68%; n=4, p<0.01) following treatment with 3% CSE at 48 h, compared with unstimulated cells. Live cell imaging demonstrated that cells underwent apoptosis in response to low dose CSE (3%, 1 h treatment) at 24 h (p=0.05) compared with unstimulated cells. Immunohistochemical analysis revealed reduced CD31 expression in the alveolar bed of emphysema tissue, indicating capillary loss. Regional alveolar expression of VEGF-R2 was also reduced compared with non-emphysematous tissue. Caspase-3 staining revealed positive cells in the alveolar bed, a sub-population of these indicating the presence of apoptotic endothelial cells in severe emphysema. Conclusions: Microvascular endothelial cells isolated from individuals with emphysema undergo accelerated apoptosis and down-regulate VEGF-R2 in response to CSE. These findings were consistent with the immunohistochemical analysis of emphysema tissue. This may represent a maladaptive response to CSE injury in susceptible individuals and be important in the pathogenesis of emphysema.